2015
DOI: 10.1016/j.pharmthera.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic pulmonary fibrosis: Recent advances on pharmacological therapy

Abstract: Idiopathic pulmonary fibrosis (IPF) is the most common and lethal of the idiopathic interstitial pneumonias with an estimated 5-year survival of approximately 20%. In the last two decades our understanding of disease pathogenesis has substantially evolved and novel compounds have been developed consequent to the increasing knowledge of the mechanisms underlying disease pathobiology. The disease appears to be driven - following chronic injury - by abnormal/dysfunctional alveolar epithelial cells that promote fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 65 publications
0
43
0
Order By: Relevance
“…We took advantage of fibroblast culture and BLM-induced lung fibrosis mouse models to investigate (1) whether deletion of Chrna 7 would reduce expression of fibrogenic genes in the early stage of the BLM-induced lung fibrosis mouse model, (2) whether deletion of Chrna 7 would attenuate collagen deposition (Masson′s trichrome staining) in BLMinduced lung fibrosis, and (3) whether activation of α7 nAChR would regulate TGF-β signaling and transcription of fibrogenic genes. The results of this study will provide novel therapeutic targets for combating lung fibrosis.…”
mentioning
confidence: 99%
“…We took advantage of fibroblast culture and BLM-induced lung fibrosis mouse models to investigate (1) whether deletion of Chrna 7 would reduce expression of fibrogenic genes in the early stage of the BLM-induced lung fibrosis mouse model, (2) whether deletion of Chrna 7 would attenuate collagen deposition (Masson′s trichrome staining) in BLMinduced lung fibrosis, and (3) whether activation of α7 nAChR would regulate TGF-β signaling and transcription of fibrogenic genes. The results of this study will provide novel therapeutic targets for combating lung fibrosis.…”
mentioning
confidence: 99%
“…Recent clinical trials showed disappointing results in treatment of IPF due to its complications highlighting the importance of early diagnosis and treatment of patients [10][11][12]. At present, it is not clear how saffron affects lung fibrosis according to its antioxidant and radical scavenging activity properties [13].…”
mentioning
confidence: 99%
“…Pulmonary fibrosis represents a group of devastating and largely irreversible disorders characterized by chronic inflammation and excessive deposition of collagen12. Pulmonary fibrosis is a very common end-stage manifestation of several diseases, including idiopathic pulmonary fibrosis (IPF), pulmonary hypertension, and scleroderma345.…”
mentioning
confidence: 99%